The discovery of gas-rich, dusty starbursts in luminous reddened quasars at z ∼ 2.5 with ALMA. Issue 4 (22nd November 2016) - Banerji, M.; Carilli, C. L.; Jones, G.; Wagg, J.; McMahon, R. G.; Hewett, P. C.; Alaghband-Zadeh, S.; Feruglio, C.
Abstract: We present ALMA observations of cold dust and molecular gas in four high-luminosity, heavily reddened ( A V ∼ 2.5–6 mag) type 1 quasars at z ∼ 2.5 with virial M BH ∼ 10 10 M⊙, to test whether dusty, massive quasars represent the evolutionary link between submillimetre-bright galaxies and unobscured quasars. All four quasars are detected in both the dust continuum and in the 12 CO(3-2) line. The mean dust mass is 6 × 10 8 M⊙ assuming a typical high-redshift quasar spectral energy distribution ( T = 41 K, β = 1.95 or T = 47 K, β = 1.6). The implied star formation rates are very high – ≳1000 M⊙ yr −1 in all cases. Gas masses estimated from the CO line luminosities cover ∼1–5× 10 10 (αCO /0.8)M⊙ and the gas depletion time-scales are very short – ∼5–20 Myr. A range of gas-to-dust ratios is observed in the sample. We resolve the molecular gas in one quasar – ULASJ2315+0143 ( z = 2.561) – which shows a strong velocity gradient over ∼20 kpc. The velocity field is consistent with a rotationally supported gas disc but other scenarios, e.g. mergers, cannot be ruled out at the current resolution of these data. In another quasar – ULASJ1234+0907 ( z = 2.503) – we detected molecular line emission from two millimetre-bright galaxies within 200 kpc of the quasar, suggesting that this quasar resides in a significant overdensity. The high detection rate of both cold dust and molecular gas in these sources, suggests that reddened quasars could correspond to an early phase in massive galaxy formation associated with large gas reservoirs and significant star formation.